CubMemPC: Computerized Test to Assess the Visuospatial Short-Term Memory with and without Distractors - Guevara, M. A.; Sanz - Martin, A.; Hernández - González, M.; Sandoval - Carrillo, I. K. (Revista Mexicana de Ingenieria Biomedica, 2014)
Short-term memory is a system that holds a small amount of information during seconds; it is subdivided into immediate memory if the information is only stored temporarily and working memory, if the information is stored and manipulated simultaneously. ``Corsi block task’’ is a test that has been widely used to assess visuospatial working memory; in this task, the assessed subject must remember increasing sequences of cubes touches. This article describes the operation and advantages of CubMemPc program, which is a computerized version of ``Corsi block task’’ designed to assess visuospatial short-term memory (immediate and working memory). The program makes it possible the application of different sequences of ``cube touches’’, the registration of both the subject’s responses and execution time. Besides, it allows including visual stimuli as distracters, which permit to study the effects of emotion on short-term memory. Given its availability, flexibility and manageability CubMemPc can be used by researchers in the field of cognitive neuroscience and for psychology professionals in the assessment of visuospatial immediate memory and working memory with or without distracters.